Factores de riesgo asociados a la mortalidad neonatal en una institución hospitalaria Iquitos 2022 - Pinedo Cancino, Johana Valeria (2025)
The present study entitled "Risk Factors Associated with Neonatal Mortality at the Regional Hospital De Loreto, 2022", aimed to identify the association between risk factors and the neonatal mortality rate. A quantitative, non- experimental, cross-sectional, descriptive correlational design was used. The technique used was the documentary review of the medical records of deceased neonates and neonatal mortality reports. The sample consisted of 70 medical records of deceased neonates. The results showed that 20.0% of the neonates had early neonatal mortality and 1.4% of the neonates had late neonatal mortality. Extreme prematurity was the most prevalent factor in cases of neonatal mortality. A significant relationship was found between gestational age and neonatal mortality, applying Kendall's Tau b statistical test, obtaining a value of -0.183, T=-1.68 and a value of p< 0.10, which allows us to accept the hypothesis raised in the study. Concluding that there is a significant relationship between gestational age and neonatal mortality. Extreme prematurity was a determining factor in most cases of neonatal mortality, underscoring the importance of implementing specific interventions to improve neonatal health outcomes in this population.